Human Work Interaction Design: Analysis and Interaction Design Methods for Pervasive and Smart Workplaces 4th IFIP 13.6 Working Conference, HWID 2015, London, UK, June 25-26, 2015, Revised Selected Papers - Abdelnour-Nocera, José; Baricelli, Barbara Rita; Lopes, Arminda; Campos, Pedro; Clemmensen, Torkil (IFIP Advances in Information and Communication Technology, 2015)
This book constitutes the thoroughly refereed post-conference proceedings of the 4th IFIP WG 13.6 Working Conference on Human Work Interaction Design, HWID 2015, held in London, UK, in June 2015. The 15 revised full papers presented were carefully selected for inclusion in this volume. The papers reflect many different areas and address many complex and diverse work domains, focusing on the integration of work analysis and interaction design methods for pervasive and smart workplaces. They are organized in the following sections: methodologies; environment, and specific contexts. .